Exploring Learners’ Views on the Role of AI in Translation Practices - Richard Ferry Nugraha; Natalina Asi; Akhmad Fauzan (JADEs Journal of Academia in English Education, 2026)
The development of Artificial Intelligence (AI) is rapidly transforming the landscape of language education. Specifically, on the context of translation courses, the presence of AI is inevitably affecting the practices of translation by emerging various perceptions on it. Hence, this study aims to explore the Indonesian EFL students’ views on the role of AI in translation practices. Using the mixed method with sequential explanatory (Creswell & Clark, 2017), data were gathered through a Likert Scale questionnaire administered to 100 students from two Translation Courses in English Language Education Study Program at a state university in Central Kalimantan, Indonesia. The findings reveal a dichotomy in students’ perceptions: while some view AI as a beneficial tool that enhances efficiency and accuracy, others express concerns about its potential to diminish language skills, creativity, and the role of human translators. These mixed perceptions highlight the need for a balanced approach in integrating AI into translation education, ensuring that students develop both technological proficiency and critical translation skills. The study’s implications suggest a reconsideration of curriculum design, emphasizing the complementary roles of AI and human expertise in fostering well-rounded translators.